Using problem-based learning in a Chinese character class design: A case study of Korean learners of Chinese. (June 2019) - Jang, Eun Young; Park, Heung Soo; Jeong, Yeon Sil
This study attempted to try out Chinese-character education centering on experience and learners away from existing lecture-centered, teacher-centered education. For this purpose, problem-based learning (PBL) was proposed as one of the Chinese-language ability-enhancement measures for Korean learners of the Chinese language, and in order to examine the effect, we attempt to use the PBL tasks in the 'Chinese-language reading' class at a university for basic Chinese-language learners and analyze the results. PBL is a teaching-learning method in which learners focus on learning by using problems. In this study, we attempted to use PBL for the group work format. In this way, we can confirm that the class using the PBL has many advantages, such as improving learning ability and problem-solving ability, and strengthening cooperation. In addition, it was found that PBL is worthwhile to try because it is effective in inducing learning motivation, improving attention and interest in Chinese-character learning, improving learning attitudes of learners, and developing self-directed learning abilities.